KARAKTERISTIK MIKROKAPSUL MINYAK ATSIRI LENGKUAS DENGAN MALTODEKSTRIN SEBAGAI ENKAPSULAN [Characteristics of Galangal Essential Oil Microencapsulation Using Maltodextrin Encapsulant] - . Supriyadi; A. Sakha Rujita (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Research on encapsulation of galangal (Alpinia galanga) essential oil using maltodextrin as a coating substance was aimed to determine the ideal proportion between the essential oil and coating material to produce microcapsules, and to determine its characteristics.The ratio of galangal essential oil and maltodextrin studied were 1:8, 1:10, and 1:12. Emulsification was performed using Turrax homogenizer at 11.500 rpm for 2 min. Microencapculation was performed by spray drying at inlet and outlet temperatures of 120 and 80°C, respectively, and feed flow rate of 15 mL/min. The optimum conditions for microcapsules were determined based on the water content, aw value, surface- and entrapped-oil, and volatile compounds profile (total volatile and volatile composition) of the microcapsules. Microcapsules prepared by essential oil and maltodextrin at a ratio of 1:10 was found to have better characteristics. The microcapsules had a moisture content of 6.27%, aw of 0.49, surface oil of 1.22 and total volatile of 42.22%. Methyl cinnamate, 1.8-cineole, a-pinene and b-pinene were found as the main volatile constituents in both of essential oil and microcapsules. Methyl cinnamate was more stable than the other volatile compounds, even after encapsulation process.